Analisis Relasi Antara Petani dan Tengkulak Dalam Usahatani Jagung Hibrida - Pira Yuniar; Rasyidah Bakri; Eymal B. Demmallino; A. Amrullah (Hasanuddin University, 2026)
Corn is one of the strategic food commodities that serves as a primary source of livelihood for communities in Soppeng Regency. In marketing their harvest, farmers generally sell corn to middlemen who act as intermediaries between farmers and the market. Previous studies have shown that the relationship between farmers and middlemen is generally influenced by capital assistance and debt arrangements. However, the phenomenon observed in Goarie Village, Marioriwawo District, Soppeng Regency indicates that farmers continue to sell their harvest to middlemen even though capital is not always the primary basis of their relationship. This study aims to analyze the relationship between farmers and middlemen in hybrid corn farming in Marioriwawo District, Soppeng Regency. This study employed a descriptive qualitative approach using Social Exchange Theory. Informants were selected through purposive sampling and consisted of 11 participants, including eight hybrid corn farmers and three middlemen. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the relationship between farmers and middlemen is established through the marketing of harvested corn, the exchange of price information, trust, and capital. This relationship is maintained because it provides mutual benefits for both parties. Capital is not the dominant factor, as most farmers rely on their own financial resources to conduct farming activities. Keywords: Relationship between Farmers; Middleme;, Hybrid Corn Farmin;, Agricultural Product Marketing; Qualitative Research.